Desarrollo de software educativo como apoyo didáctico en el área de estudios sociales del nivel de educación general básica, enmarcado a los hechos históricos, geográficos y educativos del cantón Catamayo de la provincia de Loja de la región sur del Ecuador, 2011 - Yaguana Montaño, Mayra Alexandra (2012)
The present research work of thesis denominated "DEVELOPMENT OF EDUCATIONAL SOFTWARE MULTIMEDIA LIKE DIDACTIC SUPPORT IN THE AREA OF SOCIAL STUDIES OF THE LEVEL OF BASIC GENERAL EDUCATION, FRAMED TO THE HISTORICAL, GEOGRAPHICAL AND EDUCATIONAL FACTS OF THE CATAMAYO CITY LOJA PROVINCE OF THE SOUTH REGION OF THE ECUADOR, 2011", it had as objectives "To Contribute in the boys and girls of the Basic Level of the Educational Institutions and citizenship of the Catamayo city, with information about the historical review, geographical situation, cultural, architectural aspects, illustrious characters, civic identity, educational and public institutions, tourist attractiveness and parishes that conform it; to develop an applicative multimedia with the mentioned aspects and to diffuse the multimedia in the institutions of the Catamayo city, as well as in the Loja province" with the purpose to get real learnings. It is completed the objectives, by means of interviews to the habitants and officials of the Autonomous Government of Catamayo. The methodology was applied in cascade for the development of the application, the same ones that was subjected to an internal and external evaluation through a model that valued technical, aesthetic, pedagogic and informative aspects; the results of this evaluation generate suggestions and they allowed to improve the quality of the applicative. As final phase it was emitted conclusions like to motivate the students, to be critical and analytic entities, contrasting the past with the present according to the contents of the multimedia that they go approaching; to rescue the cultural identity; and it is recommended to publish the final product to avoid the loss of the social value, effort, resources and the results of the investigation research.